How frequent are non-evidence-based health care beliefs in chiropractic students and do they vary across the pre-professional educational years - Innes, Stanley I. (Chiropr Man Therap, 2018)
BACKGROUND: Evidence suggests that a students’ beliefs already prior to entering a program may be important as a determinant in sustaining unsuitable health care beliefs. Our objectives were to investigate the proportion of Australian chiropractic students who hold non-evidence-based beliefs in the first year of study and the extent to which they may be involved in non-musculoskeletal health conditions. Finally, to see if this proportion varies over the course of the chiropractic program. METHOD: In 2016, students from two Australian chiropractic programs answered a questionnaire on how often they would give advice on five common health conditions in their future practices as well as their opinion on whether chiropractic spinal adjustments could prevent or help seven health-related conditions. RESULTS: From a possible 831 students, 444 responded (53%). Students were highly likely to offer advice (often/quite often) on a range of non-musculoskeletal conditions. The proportions were lowest in first year and highest the final year. Also, high numbers of students held non-evidence-based beliefs about ‘chiropractic spinal adjustments’ which tended to occur in gradually decreasing in numbers in sequential years, except for fifth year when a reversal of the pattern occurred. CONCLUSIONS: New strategies are required for chiropractic educators if they are to produce graduates who understand and deliver evidence-based health care and able to be part of the mainstream health care system. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12998-018-0178-y) contains supplementary material, which is available to authorized users.